Ergonomics in "remote work" activities: a workstation adaptation case study in Brazil - Arruda, Poliana Nascimento (2022)
The coronavirus disease 2019 (COVID-19) pandemic decreed by the outbreak of the new coronavirus culminated in the need to implement jobs in the homes of employees who had to adhere to the “remote work” style, due to social isolation actions in Brazil. Many of the employees started to work in the absence of adequate working conditions in their homes, impacting the three dimensions of ergonomics, i.e., physical, organizational and cognitive. The objective of this chapter is to report the adjustments made in a workplace after the change of modality from face-to-face (f2f) activities to “remote work” after the beginning of the pandemic in 2020, aiming to adopt actions aimed at ergonomics. The research was carried out with a professional in the area of Environmental and Sanitary Engineering who started remote work in March 2020. The work is of a qualitative nature, using photos to illustrate the changes occurring before and after the installation of the equipments and reports on strategies to improve working conditions in the “remote work”. The cost of physical adaptations was also computed. The most reported complaints collected by the professional were back pain, neck, forearm, wrist and eye pain, in addition to mental fatigue. The necessary equipment and furniture were acquired for the physical adaptation of the workspace. Issues of working hours, days off, means of communication were also addressed, but aspects of cognitive and organizational ergonomics must have the participation of the entire work group to achieve effective results. The accompaniment of a specialized technical professional would be important for the establishment of further assertive actions, seeking the productivity and quality of life of the employee.